NAGA IDENTITY POETICS IN CONTEMPORARY NAGA ENGLISH LITERATURE (A KALEIDOSCOPIC VIEW) - Biswas, Sankar (International Journal of Research -GRANTHAALAYAH, 2020)
The Nagas originally a Sino-Mongoloid tribe are substantiated to have originated around 10th century B.C. in the plains between Huang Ho and Yangtze Ho in North Central China. As migration is a process which is reported to have been going on since time immemorial, the Nagas too could not have isolated themselves from being a part of the mass odyssey from their homeland with the anticipation of exploring and settling in naturally upgraded habitats. Hence today, the Nagas have been found to inhabit the banks of Chindwin and Irawaddy Rivers in Myanmar, and Nagaland in India. As far as their language is concerned, it is said to be an affiliate of the greater branch of Sino-Tibetan besides sharing certain similarities with Tibeto-Burman languages. As for the etymology of the word Naga is concerned, it is said to have been derived from either of the Sanskrit word namely Nagna or Nag with respective meanings ‘naked’ or ‘mountain. Frankly speaking both the etymons in question validate the universally recognized conception of Naga identity. Nagaland itself is dotted with multiple number of hills and a faction of people among all the Naga Tribes are said to have been still embracing primitivism. But what is most conspicuous about the Nagas is that though today we know Nagaland as a self-Governing state, the fact can never be contradicted that Nagas have never considered themselves part of India despite the state being taken over by India in 1952. Right from their partially being colonized by the British in the middle of the 19th century, to their strict resistance to both the British-Indian Government and then to the post-Independence Indian Government, the Nagas have shown that their assimilation to Indian mainstream is a daunting and cumbersome exercise. The origin of the Naga National Council, preceded by the armed resistance movement of Rani Gyindulu and that of the genesis of National Socialist Council of Nagaland simply bespeak that this prospect of wholesale assimilation into Indian Sense of Nationality will await the elapse of an elongated stretch of historical time. This very aspect has been enjoying international attention and the literary activists of Nagaland such as Dr Temsula Ao and Dr Easterine Kire have contributed a lot through their literary output in harnessing this aspect, throwing new critical insights into the same. This avouched denial cum resistance to be assimilated into the greater Indian National Fabric is one of the many facets of Naga Identity which also encompasses other cultural traits such as patriarchal ideology, Naga Heraka Practices, Animism, Mythogenesis and Head-Hunting Practices. Objective of this write-up: This write-up endeavours its best to foreground the very traits of Naga Identity Poetics by taking into consideration selective but relevant literary fabrications, the brainchilds of one of the two internationally recognized Naga Writers, Dr Easterine Kire with the other being Dr Temsula Ao. Methodology: This write-up is built upon the selective reading of the summary of the novels and poems of both the writers with selective perusal of secondary anecdotage in the form of critical essays, the Naga History of Independence and Naga Anthropology.